Central sleep apnoea and periodic breathing in heart failure: prognostic significance and treatment options. (11th October 2019) - Randerath, Winfried; Deleanu, Oana; Schiza, Sofia; Pepin, Jean-Louis
Central sleep apnoea (CSA) including periodic breathing is prevalent in more than one-third of patients with heart failure and is highly and independently associated with poor outcomes. Optimal treatment is still debated and well-conducted studies regarding efficacy and impact on outcomes of available treatment options are limited, particularly in cardiac failure with preserved ejection fraction. While continuous positive airway pressure and oxygen reduce breathing disturbances by 50%, adaptive servoventilation (ASV) normalises breathing disturbances by to controlling the underlying mechanism of CSA. Results are contradictory regarding impact of ASV on hard outcomes. Cohorts and registry studies show survival improvement under ASV, while secondary analyses of the large SERVE-HF randomised trial showed an excess mortality in cardiac failure with reduced ejection fraction. The current priority is to understand which phenotypes of cardiac failure patients may benefit from treatment guiding individualised and personalised management. CSA in heart failure impairs outcome, but optimal treatment is intensively debated. Increasing evidence may guide to differentiation and individualised therapy of phenotypes according to differences in pathophysiology and treatment response. http://bit.ly/2kvTepX